Allozyme and DNA sequence comparisons of nine species of Encephalartos (Zamiaceae) - Bank, F. H. van der; Wink, Michael; Treutlein, Jens (Biochemical systematics and ecology, 2001)
Phylogenetic relationships between Encephalartos altensteinii Lehmann, E. arenarius R.A. Dyer, E. horridus (Jacquin) Lehmann, E. latifrons Lehmann, E. lehmannii Lehmann, E. longifolius (Jacquin) Lehmann, E. princeps R.A. Dyer and E. trispinosus (Hooker) R.A. Dyer were studied, using E. ferox Bertoloni f. as outgroup. Three continuous and one discontinuous buffer systems were used and gene products of 14 enzyme coding loci were examined by horizontal starch gel-electrophoresis. Genetic variation was studied in a cultivated population of E. lehmannii and the average heterozygosity value for this population is 13.5%, which falls within the range reported for other cycad species. Fixed allele differences between the species studied was not found at any of the loci studied, which suggest that these species are closely related. DNA sequence analysis of rbcL and ITS 1 & 2 genes (1428 and 895 basepairs, respectively) confirmed the close genetic relationships between these taxa. According to ITS and rbcL sequences E. altensteinii and E. princeps are sibling taxa which form a sister group to E. arenarius, E. horridus, E. latifrons, E. lehmannii, E. longifolius, and E. trispinosus. The genetic distances between both groups were 0.12-0.47% for ITS and 0.08-0.16% for rbcL DNA. The results indicate recent (probably pleistocenic) speciation for this group of cycads, and the relationships are discussed with reference to affinities based on morphology and distribution.